Strategic Community Development Through Corporate Social Responsibility: A Case Study of the Regional Dance Program at SDN Sawotratap Sidoarjo by PT. PLN Indonesia Power - Hilda Sri Rahayu; Atef Fahrudin; Amna Amna; Ade Nurhayati Kusumadewi; Umban Adi Jaya (INJECT (Interdisciplinary Journal of Communication), 2025)
This study aims to examine Corporate Social Responsibility in the empowerment initiative of regional dance at SDN Sawotratap, Sidoarjo. The purpose of this study focuses on how stakeholder theory analysis is carried out in the Corporate Social Responsibility empowerment program of Regional Dance at SDN Sawotratap Sidoarjo, by combining cross-cultural communication theory and stakeholder theory, which emphasizes people, profit, and planet. The method used is qualitative research, specifically the case study approach, to collect data through observation and interviews. The analysis is based on stakeholder theory, the concept of the Triple Bottom Line, and cross-cultural communication theory. The findings of this study indicate that the Corporate Social Responsibility efforts of PT PLN Nusantara Power Services have involved various stakeholders, both internal and external, including teachers and students, as well as corporate communication and CSR initiatives within PT PLN Nusantara Power Services. The impact of this CSR empowerment program can positively contribute to the sustainability of the CSR community empowerment program, in this case, through the preservation of culture and community participation, in line with the objectives of the study related to stakeholder theory in the implementation of corporate social responsibility initiatives of regional dance in community empowerment programs.